NEW RANGE RESEARCH OF PHYSICAL AND MECHANICAL PROPERTIES OF KNITTED FABRICS (International Conference on Economics, Finance, Banking and Management, 2025)
In order to effectively use local raw materials in scientific work, research was conducted on the physical and mechanical properties of two-layer knitted fabrics with a new structure made of pan yarn.